Do high flexion posterior stabilised total knee arthroplasty designs increase knee flexion? A meta analysis - Sumino, Takanobu (Springer-Verlag, 2011)
PURPOSE: This systematic literature review analysed the change in range of knee flexion from pre-operative values, following conventional posterior stabilised (PS) and high-flexion (H-F) PS total knee arthroplasty (TKA). METHODS: We calculated the weighted mean differences of pre- and postoperative flexion using meta-analysis with random effect modelling. Eighteen studies met our inclusion criteria. These data included a total of 2,104 PS knees that received conventional implants and 518 knees that received H-F implants. RESULTS: The pooled gain in flexion was 4.70° in the conventional group (p <0.0001) and 4.81° in the H-F group (p = 0.0008). In the subgroup analysis, the Western patient group showed significant difference in the gain of flexion with both implants. In contrast, no significant gain in flexion was observed in the Asian patient group. CONCLUSIONS: These results suggest that improvement of preoperative flexion after TKA using current H-F PS prostheses is similar to that of conventional PS prostheses.